2021
DOI: 10.3390/ijms22063019
|View full text |Cite
|
Sign up to set email alerts
|

In Ovarian Cancer Multicellular Spheroids, Platelet Releasate Promotes Growth, Expansion of ALDH+ and CD133+ Cancer Stem Cells, and Protection against the Cytotoxic Effects of Cisplatin, Carboplatin and Paclitaxel

Abstract: A high platelet count is associated with a poor prognosis in ovarian cancer (OvCa). Despite good clinical responses with platinating agents in combination with taxanes, numerous OvCa patients relapse due to chemotherapy resistance. Here, we report that treatment of OvCa cells A2780, OVCAR5 and MDAH with releasate from activated platelets (PR) promoted multicellular tumor spheroid (MCTS) formation. These OvCa-MCTSs had increased percentages of CD133+ and aldehyde dehydrogenase (ALDH)+ cells, bona fide markers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…A poly-HEMA coating in culture flasks has been used for the production of 3D heterotypic models of normal ovary and to study early ovarian cancer development ( Lawrenson et al, 2012 ). Ovarian cancer cell lines grown under poly-HEMA conditions in the presence of activated platelet releasate, formed spheroids faster and were more resistant to the chemotherapeutic agents cisplatin, carboplatin and paclitaxel ( Casagrande et al, 2021 ).…”
Section: 3d In Vitro Ovarian Cancer Modelsmentioning
confidence: 99%
“…A poly-HEMA coating in culture flasks has been used for the production of 3D heterotypic models of normal ovary and to study early ovarian cancer development ( Lawrenson et al, 2012 ). Ovarian cancer cell lines grown under poly-HEMA conditions in the presence of activated platelet releasate, formed spheroids faster and were more resistant to the chemotherapeutic agents cisplatin, carboplatin and paclitaxel ( Casagrande et al, 2021 ).…”
Section: 3d In Vitro Ovarian Cancer Modelsmentioning
confidence: 99%
“…We did not observe an association between the numbers of cells expressing only CD133 or only ALDH and clinical characteristics, but a high number of stem-like CD133+ALDHhigh cells before treatment were associated with a reduced progression-free survival in a multivariable analysis. It has previously been shown that platelets invert the cytostatic effects of carboplatin and paclitaxel on CD133+ and ALDH+ OC cells by secreting a number of cytokines and growth factors, in non-adherent conditions [ 46 ]. Further research is needed to understand the mechanisms of the interaction between OC circulating stem cells and other blood components.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plateletderived chemokine RANTES and TSP1 (233) both increased the survival of paclitaxel-treated cancer cells (234). Casagrande et al suggested that platelet-secreted factors ((EGF, PDGF, TGFb, IGF and CCL5) protected cancer stem cells from paclitaxel, cisplatin and carboplatin (235). All above data prove the involvement of platelets in cancer chemoresistance.…”
Section: Platelet-related Chemoresistancementioning
confidence: 91%
“…Casagrande et al. suggested that platelet-secreted factors ((EGF, PDGF, TGF-β, IGF and CCL5) protected cancer stem cells from paclitaxel, cisplatin and carboplatin ( 235 ). All above data prove the involvement of platelets in cancer chemoresistance.…”
Section: Platelet–supported Cancer Progressionmentioning
confidence: 99%